2023
DOI: 10.1021/acs.jafc.2c07391
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Calcium Overload and Activation of CaMKK/AMPK Signaling Are Related to the Acceleration of Muscle Glycolysis of Broiler Chickens Subjected to Acute Stress

Abstract: The current study investigated the effect of preslaughter transport on stress response and meat quality of broilers and explored the underlying mechanisms involved in the regulation of muscle glycolysis through calcium/calmodulin-dependent protein kinase kinase (CaMKK)/AMP-activated protein kinase (AMPK) signaling. Results suggested that transport induced stress responses of broilers and caused PSE-like syndrome of pectoralis major muscle. Preslaughter transport enhanced the mRNA expressions of glycogen phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The content of these carbohydrates at this point of time is usually quite low, but also very variable. For example, the glycogen or glucose contents are 5 to 15 µmol/g or 3 to 9 µmol/g in chicken breast muscles [51][52][53], 10 to 20 µmol/g or 7 to 15 µmol/g in the porcine M. longissimus lumborum (LT) [54][55][56][57] and 4 to 16 µmol/g or 5 to 6 µmol/g in the bovine LT [58,59]. Immonen et al [60] found residual glycogen values between 20 µmol/g and 60 µmol/g meat.…”
Section: Discussionmentioning
confidence: 99%
“…The content of these carbohydrates at this point of time is usually quite low, but also very variable. For example, the glycogen or glucose contents are 5 to 15 µmol/g or 3 to 9 µmol/g in chicken breast muscles [51][52][53], 10 to 20 µmol/g or 7 to 15 µmol/g in the porcine M. longissimus lumborum (LT) [54][55][56][57] and 4 to 16 µmol/g or 5 to 6 µmol/g in the bovine LT [58,59]. Immonen et al [60] found residual glycogen values between 20 µmol/g and 60 µmol/g meat.…”
Section: Discussionmentioning
confidence: 99%